2020
DOI: 10.1021/acs.jpcc.0c07243
|View full text |Cite
|
Sign up to set email alerts
|

Structural Correlations in Jahn–Teller Systems of Mn3+ and Cu2+: Unraveling Local Structures through Spectroscopic Techniques

Abstract: An experimental correlation study between the low-symmetry 3d orbital splitting pattern, Δe and Δt, determined by optical spectroscopy, and the local distortion ρ, determined by X-ray diffraction, for different Cu2+ and Mn3+ fluorides and chlorides is presented. Single crystals of different dimensionalities were explored, some of them studied under high-pressure conditions. The collection of structural and spectroscopic data provides structural correlations relating ρ and Δe and Δt in Cu2+ and Mn3+ systems, sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 85 publications
2
6
0
Order By: Relevance
“…Mn(d x 2 Ày 2 )c haracter (Figure 4). Form any Mn III systems exhibiting Jahn-Teller distortion, [17] similar energy splitting were reported between occupied Mn(d z 2 )a nd unoccupied Mn(d x 2 Ày 2 )orbitals.Since ab initio calculations underestimate the gap,the Mn(d z 2 )!Mn(d x 2 Ày 2 )gap corresponds well to the Mn(d-d) band observed at 508 nm by ellipsometry [10e, 15] and in OD data (Figure S1). Thet ail of this band extends above 650 nm (1.9 eV).…”
Section: Methodssupporting
confidence: 71%
“…Mn(d x 2 Ày 2 )c haracter (Figure 4). Form any Mn III systems exhibiting Jahn-Teller distortion, [17] similar energy splitting were reported between occupied Mn(d z 2 )a nd unoccupied Mn(d x 2 Ày 2 )orbitals.Since ab initio calculations underestimate the gap,the Mn(d z 2 )!Mn(d x 2 Ày 2 )gap corresponds well to the Mn(d-d) band observed at 508 nm by ellipsometry [10e, 15] and in OD data (Figure S1). Thet ail of this band extends above 650 nm (1.9 eV).…”
Section: Methodssupporting
confidence: 71%
“…The optical transitions 81→89 and 82→90, calculated around 1.9 eV for α spins, have therefore a strong Mn(dz2 )→Mn(dx2-y2 ) character (Figure 4). For many Mn III systems exhibiting Jahn–Teller distortion, [17] similar energy splitting were reported between occupied Mn(dz2 ) and unoccupied Mn(dx2-y2 ) orbitals. Since ab initio calculations underestimate the gap, the Mn(dz2 )→Mn(dx2-y2 ) gap corresponds well to the Mn(d‐d) band observed at 508 nm by ellipsometry [10e, 15] and in OD data (Figure S1).…”
Section: Resultssupporting
confidence: 70%
“…Experimentally, it has been found that 10 Dq depends on R – t , where the exponent t is often found to be close to 5 . By this reason, it is still claimed that the exponent t mainly comes from the CF contribution , despite this approach leading to 10 Dq values much smaller than experimental ones …”
Section: Introductionmentioning
confidence: 99%
“…Tetragonal CuF 6 4– units are also formed in Cu 2+ -doped K 2 ZnF 4 or Ba 2 ZnF 6 -layered perovskites though there is no Jahn–Teller effect as the a 1g (∼3 z 2 – r 2 ) and b 1g (∼ x 2 – y 2 ) levels are not degenerate following the tetragonal symmetry of the host lattice . Accordingly, the theory describing the Jahn–Teller effect , cannot, in general, be transferred ,, to understand pure layered compounds such as the orthorhombic K 2 CuF 4 or Cs 2 AgF 4 . , Nevertheless, the Jahn–Teller framework is still surprisingly applied to d 9 ions under tetragonal or lower symmetries.…”
Section: Introductionmentioning
confidence: 99%